Development Learning Instrument of Algebraic Structure based on Resitation Task to Improve Activities and Learning Procces - Sholikhakh, Rizqi Amaliyakh; Utami, Wikan Budi (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this research is to design an Algebra Structure learning instrument based on recitation task to improve the students' validity, practical, and effective student process and activeness skills. Through the learning tools is designed a learning that makes students repeat and reread the concepts and related theorems before the learning process Algebra Structure starts with a guide module and student duty sheet. This type of research is development research according to Borg and Gall. Data analysis was done based on validation, observation, questionnaire, interview and test. The result of this research is learning device that has developed validation value more than four. Learning tools are said to be practice & effective, there is a difference in learning achievement between the experimental class and the control class.